Best Answer

9x + 4 = 6

9x = 6 -4

9x = 2

x = 2/9

Q: WHAT DOES '' x '' equal in the equation 9x plus 4 equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

In this equation, x=6.

Multiply first equation by 3: 9x + 15y = 63Add that and second equation: 19y = 57Divide by 19: y = 3, so x = 2

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

9x + 3y = -54 3y = -9x - 54 y = -(3x + 18) Therefore, the y-intercept of this equation is y=-18.

9x+3y = 6 3y = -9x+6 y = -3x+2 which is now in slope-intercept form

Related questions

Multiply the first equation by 3 to give 9x + 15y = 21

In this equation, x=6.

If: 12 = 9x+3 Then: 12-3 = 9x And: 9 = 9x So: x =1

no

The discriminant is 33.

Multiply first equation by 3: 9x + 15y = 63Add that and second equation: 19y = 57Divide by 19: y = 3, so x = 2

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

9x+3y = 6 3y = -9x+6 y = -3x+2 which is now in slope-intercept form

9x + 3y = -54 3y = -9x - 54 y = -(3x + 18) Therefore, the y-intercept of this equation is y=-18.

-38-10x = 9x+19 -38-19 = 9x+10x -57 = 19x |: 19 -3 = x Therefore x equals -3

an equation

y=9x=3it equals ......y= 3.334